DUKUNGAN SOSIAL, BEBAN KERJA DAN PEMBERIAN INSENTIF TERHADAP KINERJA PERAWAT DI RSUD Hj. ANNA LASMANAH BANJARNEGARA - Ratna Suryani; Dina Saktianingsih; Siti Maesaroh (Medikonis, 2021)
ABSTRACT The problem in this study is that nurses are the spearhead of health services in hospitals and are one of the keys to improving the quality of services in hospitals. For this reason, it is necessary to pay attention to the performance of nurses in carrying out their duties and functions in providing professional services to patients. This study aims to determine whether there is an effect of social support, workload and incentives on the performance of nurses in RSUD Hj. Anna Lasmanah Banjarnegara This study uses a quantitative approach. The data used in this research is primary data with questionnaire distribution technique. The population in this study were nurses at RSUD Hj. Anna Lasmanah Banjarnegara. The sampling technique in this study was using the slovin calculation and obtained a sample of 135 respondents. Data analysis in this study used multiple linear regression analysis with SPSS 16 software. The results showed that partially social support and workload variables had a significant effect on nurse performance. While the variable of incentives does not have a significant effect on the performance of nurses. It is known that the coefficient of determination in this study is 0.430 (43%), meaning that the percentage of the influence of independent variables, namely social support, workload and incentives on nurse performance is 43% while the remaining 57% is influenced by other variables not included in this study.